Conclusion - Prevost, Gary; Campos, Carlos Oliva; Ayerbe, Luis Fernando [UNESP]; Vanden, Harry E. (My University, 2014)
The security policy of the United States in the whole of the Western Hemisphere must be placed in its broad historic perspective with attention to the current moment of the twenty-first century. For two centuries, back to the time of Thomas Jefferson and James Monroe, leaders in Washington, DC, have viewed the hemisphere as the natural sphere of influence for the United States, a place of great economic interest for the United States in terms of investment, raw materials, and markets. That reality has not changed over two centuries, only changes over time have been in the ability of the United States to extend its dominance in the region. The part of the region closest to the United States-Mexico, Central America, and the Caribbean-came under US control in the first 30 years of the twentieth century and remain there in the twenty-first century. That control remains primarily through regional trade agreements and the newly launched security initiatives. The United States’ influence in South America has always been more fluid and it remains so in the early twenty-first century. The United States has always sought a dominant role in South America due to its vast resources and markets. In the nineteenth century and the first half of the twentieth century, the United States extended some measure of economic influence throughout South America but the reality of British and French political and economic power thwarted US domination.